Dostopnost kulture in/ali inkluzija? - Poljak Istenič, Saša (Etnolog. Nova vrsta (Ljubljana), 2015)
The article analyses two decades of efforts in Slovenia's museums and galleries to include the blind and visually impaired in their activities in the context of cultural policy and legislative demands. This museum practice today not only contributes to better accessibility of culture to vulnerable groups and their general inclusion, but also yields more positive museum experiences for all segments of visitors, widens the horizon of museum workers, and sensitizes the general public to the position of vulnerable groups in society.
Keywords: cultural heritage; kulturna dediščina; muzeji; galerije; osebe s posebnimi potrebami; slepi; slabovidni; inkluzija; dostopnost